Podcasts as a health literacy tool: an experience (Boletín Semillero de Investigación en Familia, 2022)
Learning is a process that, if we want it to be effective and lasting, must be carried out actively and with spaced repetitions. There is no doubt that a proven method to consolidate knowledge is the process of taking a leading role and instructing a third person about what was initially learned. Making use of the already established information technologies and social networks, disseminating through them information about the field in which the person is trained could, certainly, be an extraordinary way to make the disseminator grow both in the field on which that instructs as in a transversal and broad sense of other areas of training.
Keywords: problem-based learning; blogging; webcast; education; teaching.